1996
DOI: 10.1203/00006450-199607000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Proton Magnetic Resonance Spectroscopy of the Brain in Normal Preterm and Term Infants, and Early Changes after Perinatal Hypoxia-Ischemia

Abstract: The aims of this study were 1) to define normal perinatal maturational changes in proton metabolite peak-area ratios in two regions of the neonatal brain, the thalamic and occipitoparietal regions, and 2) to investigate abnormalities of these ratios after perinatal hypoxia-ischemia. Fifty-four infants were studied: 35 normal control infants at 31-42 wk of gestational plus postnatal age, and 19 "asphyxiated" infants suspected of cerebral hypoxic-ischemic injury. Proton spectra were collected at 2.4 tesla from (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
88
1
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(97 citation statements)
references
References 35 publications
5
88
1
3
Order By: Relevance
“…1). Alanine is found in spectra of pyogenic abscesses (see Table 1) and meningiomas and propanediol can accumulate with intravenous anti-seizure medications, especially in neonates (1,(8)(9)(10).…”
Section: Spectral Assignmentsmentioning
confidence: 99%
“…1). Alanine is found in spectra of pyogenic abscesses (see Table 1) and meningiomas and propanediol can accumulate with intravenous anti-seizure medications, especially in neonates (1,(8)(9)(10).…”
Section: Spectral Assignmentsmentioning
confidence: 99%
“…MRI studies of term newborns with NE show the DGN as the most severely injured area (8,28,29), which corresponds to the spatial distribution of lactate measured by 1 H-MRS (9,30). The measured cytokines were not associated with structural abnormalities detected by MRI.…”
mentioning
confidence: 99%
“…In HIE, cerebral lactate (Lac) rises as a result of anaerobic metabolism, then it is rapidly cleared on resuscitation to be followed by a secondary increase after 12-24 hours because of renewed production of Lac in brain tissue rather than entry via the circulation [22,23]. The Cr was chosen as the metabolite of reference in 1H-MRS as it is not signifi cantly changed after the onset of HIE.…”
Section: Discussionmentioning
confidence: 99%
“…The signal abnormalities of basal ganglia can be considered as an indicator of the severity of neonatal HIE, while the signal abnormality of thalamus is considered as a relatively specifi c and sensitive indicator of ischemic brain injury caused by hypoxia [21,22]. In the study of Thayyil, et al [6], the MRI of neonates with mild HIE showed normal basal ganglia with variable degrees of cortical signal abnormalities, while patients with most severe HIE showed mixed cortical and basal ganglia signal abnormalities.…”
Section: Discussionmentioning
confidence: 99%